2013
DOI: 10.1088/2041-8205/779/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

SUPERNOVA NEUTRINO NUCLEOSYNTHESIS OF THE RADIOACTIVE 92 Nb OBSERVED IN PRIMITIVE METEORITES

Abstract: The isotope 92 Nb decays to 92 Zr with a half-life of 3.47 × 10 7 yr. Although this isotope does not exist in the current solar system, initial abundance ratios for 92 Nb/ 93 Nb at the time of solar system formation have been measured in primitive meteorites. The astrophysical origin of this material, however, has remained unknown. In this Letter, we present new calculations which demonstrate a novel origin for 92 Nb via neutrino-induced reactions in core-collapse supernovae (ν-process). Our calculated resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 29 publications
(47 reference statements)
6
55
0
Order By: Relevance
“…However, initial abundance ratio of 92 Nb/ 93 Nb at the time of solar system formation has been measured in primitive meteorites. Our calculated ratio is in reasonable agreement with observation when we take account of the mixture of supernova ejecta with the protosolar cloud [16].…”
Section: Supernova ν-Process Nucleosynthesissupporting
confidence: 89%
See 2 more Smart Citations
“…However, initial abundance ratio of 92 Nb/ 93 Nb at the time of solar system formation has been measured in primitive meteorites. Our calculated ratio is in reasonable agreement with observation when we take account of the mixture of supernova ejecta with the protosolar cloud [16].…”
Section: Supernova ν-Process Nucleosynthesissupporting
confidence: 89%
“…These would be a piece of evidence for the supernova ν-process. Heavy rare elements 92 Nb, 98 Tc, 138 La and 180 Ta are also produced in the ν-process from preexisting stable nuclei mainly in the O/Ne layer [15,16]. The s-process is also suggested to produce some amount of 180 Ta (Fig.…”
Section: Supernova ν-Process Nucleosynthesismentioning
confidence: 98%
See 1 more Smart Citation
“…The neutrino process in supernovae has been suggested [1] as the mechanism for the origin of several rare isotopes of light-to-heavy elements such as 7 Li, 11 B [2], 92 Nb [3], 138 La [4], 180 Ta [5]. Copious amounts of energetic neutrinos are emitted from the proto-neutron star formed during a core-collapse supernova.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence that a short-lived radioactivity has existed at the time of the solar system formation was found by meteorite analysis but its astrophysical origin have been an open question. Recently Hayakawa et al [3] presented that the supernova neutrino process can explain its abundance using a supernova model calculation with a new neutrino reaction cross sections involved. In addition, Yoshida et al, have suggested that 7 Li/ 11 B ratio can consternate parameters for the neutrino oscillation [2].…”
Section: Introductionmentioning
confidence: 99%